2013
DOI: 10.1210/en.2013-1030
|View full text |Cite
|
Sign up to set email alerts
|

3,5-T2 Is an Alternative Ligand for the Thyroid Hormone Receptor β1

Abstract: Several liganded nuclear receptors have alternative ligands acting in a tissue-specific fashion and playing important biological roles. We present evidence that 3,5-diiodothyronine (T(2)), a naturally occurring iodothyronine that results from T(3) outer-ring deiodination, is an alternative ligand for thyroid hormone receptor β1 (TRβ1). In tilapia, 2 TRβ isoforms differing by 9 amino acids in the ligand-binding domain were cloned. Binding and transactivation studies showed that T(2) activates the human and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 42 publications
10
78
0
Order By: Relevance
“…Furthermore, hepatic in vivo expression of L-TRb1 is 10 6 -fold higher than that of S-TRb1, suggesting that, at least in teleosts, the effects of THs are mainly mediated through this isoform. These observations, together with our findings that in vivo, T 2 and T 3 modulate the expression of L-TRb1 and S-TRb1 respectively, suggest a distinct signaling pathway for each TH in teleosts and prompted us to propose an extra level in the cascade of TH signaling for which T 2 is specifically made and regulated (Mendoza et al 2013).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Furthermore, hepatic in vivo expression of L-TRb1 is 10 6 -fold higher than that of S-TRb1, suggesting that, at least in teleosts, the effects of THs are mainly mediated through this isoform. These observations, together with our findings that in vivo, T 2 and T 3 modulate the expression of L-TRb1 and S-TRb1 respectively, suggest a distinct signaling pathway for each TH in teleosts and prompted us to propose an extra level in the cascade of TH signaling for which T 2 is specifically made and regulated (Mendoza et al 2013).…”
Section: Introductionmentioning
confidence: 76%
“…Accordingly, studies from several laboratories have suggested that 3,5-di-iodothyronine (3,5-T 2 or T 2 ), a putative product of the outer ring deiodination pathway involved in T 3 metabolism, also possesses bioactivity (Goglia 2005). In fact, studies from our laboratory have shown that both T 3 and T 2 act directly on TH-dependent genes in teleost liver (García-G et al 2007) and that these genomic actions are mediated by different isoforms of TRb1 (Mendoza et al 2013). Indeed, results from binding and transactivating assays revealed that the effects of T 2 on genomic regulation appear to be mediated by a different isoform of TRb1 that is found only in fish and contains a 9-amino acid insert in its ligand-binding domain, and which we have denominated long TRb1 (L-TRb1).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In particular, this link is in accordance with animal studies showing that 3,5-T2 was only a third as potent as T3 in suppressing TSH concentrations, and rather high pharmacological 3,5-T2 concentrations are required for TSH suppression (34)(35)(36). However, several animal studies in rodents and other species, for example killifish, indicated that 3,5-T2 interferes with the hypothalamus-pituitary-thyroid axis at several levels such as pituitary, thyroid, and peripheral action, thereby displaying a broad spectrum of mechanisms involved such as classical interaction with TR and also rapid effects at the cell membrane and mitochondria (10,12,14,(34)(35)(36)(37)(38)(39)(40) (for a review, see (3)). Action of 3,5-T2 via these different targets and molecular mechanisms might occur at different 3,5-T2 concentrations and depend on acute or chronic exposure (35,37,40), thus possibly explaining the unexpected bell-shaped relationship with serum TSH.…”
Section: Discussionmentioning
confidence: 99%